Examining Associations Between COVID-19 Experiences and Posttraumatic Stress. Issue 8 (17th November 2021) - Gallagher, Matthew W.; Smith, Lia J.; Richardson, Angela L.; Long, Laura J.
Abstract: COVID-19 has had a profound impact on health and well-being worldwide. There is an increasing need to understand the psychological impact of COVID-19, particularly associations with posttraumatic stress. This cross-sectional study examined associations between COVID-19 and posttraumatic stress among adults utilizing structural equation modeling methods. Results demonstrated that COVID-19 experiences were consistently associated with increased odds of exhibiting posttraumatic stress and higher expressions of total posttraumatic stress. COVID-19 related stress was also robustly associated with posttraumatic stress. These initial findings suggest that COVID-19 is associated with high expression of posttraumatic stress symptomatology, underscoring the increased need for mental health services.